Sex Differences in Short-Term Outcomes After Acute Ischemic Stroke. Issue 2 (February 2015) - Irie, Fumi; Kamouchi, Masahiro; Hata, Jun; Matsuo, Ryu; Wakisaka, Yoshinobu; Kuroda, Junya; Ago, Tetsuro; Kitazono, Takanari; Ishitsuka, Takao; Fujimoto, Shigeru; Ibayashi, Setsuro; Kusuda, Kenji; et al.
<x xml:space="preserve">Abstract</x> Background and Purpose— Variable sex differences in clinical outcomes after stroke have been reported worldwide. This study aimed to elucidate whether sex is an independent risk factor of poor functional outcome after acute ischemic stroke. Methods— Using the database of patients with acute stroke registered in the Fukuoka Stroke Registry in Japan from 1999 to 2013, 6236 previously independent patients with first-ever ischemic stroke who were admitted within 24 hours of onset were included in this study. Baseline characteristics were assessed on admission. Study outcomes included neurological improvement, neurological deterioration, and poor functional outcome (modified Rankin Scale score, 3–6 at discharge). Logistic regression analyses were performed to evaluate the association between sex and clinical outcomes. Results— Overall, 2398 patients (38.5%) were women. Severe stroke (National Institutes of Health Stroke Scale score, ≥8) on admission was more prevalent in women than in men. The frequency of neurological improvement or deterioration during hospitalization was not different between the sexes. After adjusting for possible confounders, including age, stroke subtype and severity, risk factors, and poststroke treatments, it was found that female sex was independently associated with poor functional outcome at discharge (odds ratio, 1.30; 95% confidence interval, 1.08–1.57). There was heterogeneity of the association between sex and poor outcome according to age: women had higher risk of poor outcome than men among patients aged ≥70 years, but no clear sex difference was found in patients aged <70 years. Conclusions— Female sex was associated with the risk of poor functional outcome at discharge after acute ischemic stroke.